Use of Oral Miltefosine for Cutaneous Leishmaniasis in Canadian Soldiers Returning from Afghanistan - Yoav Keynan; Oscar E Larios; Marni C Wiseman; Marie Plourde; Marc Ouellette; Ethan Rubinstein (Canadian Journal of Infectious Diseases and Medical Microbiology)
Old world cutaneous leishmaniasis (CL) is caused by Leishmania major and Leishmania tropica, and is endemic to several Asian and Middle-Eastern countries where the rates of infection can be substantial. CL is one of the most common vector-transmitted parasitic infections in Afghanistan. Six cases of CL in Canadian soldiers returning from Afghanistan are reported in the present study. Their lesions did not improve with fluconazole therapy, and the organism demonstrated in vitro resistance. Oral miltefosine seemed effective.